1979
DOI: 10.1111/j.1365-2494.1979.tb01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Silage and milk production: comparisons between grass silage of three different chop lengths

Abstract: Three grass silages of different chop lengths made from a uniform sward of S23 perennial ryegrass were compared in four experiments including a feeding experiment with twelve lactating cows, an eating behaviour study, a rate of passage investigation and a selection trial. The silages had median chop lengths of 9-4. 17-4 and 720 mm, termed short, medium and long, with pH values of 3-93, 3-94 and 417 and D-values of 659, 65-2 and 64 4 respectively.The daily intakes of silage DM and the daily milk yields increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
25
1
2

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 24 publications
11
25
1
2
Order By: Relevance
“…In Experiment 3 the time the cows spent eating silage was 180 min daily and was much shorter than that observed by Campling (1966), Castle et al, (1979) and Castle et al, (1981) with dry cows offered silage ad libitum. There was an appreciable variation in rate of eating silage with coefficients of variation of 24% and 38% with the low and high amounts of barley, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…In Experiment 3 the time the cows spent eating silage was 180 min daily and was much shorter than that observed by Campling (1966), Castle et al, (1979) and Castle et al, (1981) with dry cows offered silage ad libitum. There was an appreciable variation in rate of eating silage with coefficients of variation of 24% and 38% with the low and high amounts of barley, respectively.…”
Section: Discussioncontrasting
confidence: 67%
“…The highest number of ruminating periods reported in the literature ranged from 14 to 18. These numbers have been found with ad libitum feeding of grass silage, hay or straw in a long physical form to cows Campling, 19666;Castle et al, 1979Castle et al, , 1981.…”
Section: The Ckewitig Activitymentioning
confidence: 92%
“…These have shown that while wilting prior to ensiling will improve dry matter (DM) intake it does not generally improve milk output and in some instances will reduce output (Gordon, 1980;Gordon, 1981;Castle and Watson, 1982), when compared to well preserved, unwilted material. In addition, alterations to the degree of chopping or laceration of silage have not been found to influence milk output at this Institute (Gordon, 1982;Gordon and Unsworth, 1985), although small increases in yield have been reported following fine chopping in some trials elsewhere (Dulphy and Demarquilly, 1975;Castle et al, 1979), and especially when compared with silages of very long particle length (Murphy, 1983).…”
Section: Introductionmentioning
confidence: 92%